2015
DOI: 10.2147/cmar.s46042
|View full text |Cite
|
Sign up to set email alerts
|

Review of advanced catheter technologies in radiation oncology brachytherapy procedures

Abstract: The development of new catheter and applicator technologies in recent years has significantly improved treatment accuracy, efficiency, and outcomes in brachytherapy. In this paper, we review these advances, focusing on the performance of catheter imaging and reconstruction techniques in brachytherapy procedures using magnetic resonance images and electromagnetic tracking. The accuracy of catheter reconstruction, imaging artifacts, and other notable properties of plastic and titanium applicators in gynecologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 115 publications
(117 reference statements)
0
46
0
1
Order By: Relevance
“…show that the positioning error is proportional to dnormalFG4 and Zhou et al. show that the combination of large field generator distances and interferences of a typical brachytherapy environment yields the largest error 19, 20. The data at dnormaltable=120mm and over all d FG reported in Fig.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…show that the positioning error is proportional to dnormalFG4 and Zhou et al. show that the combination of large field generator distances and interferences of a typical brachytherapy environment yields the largest error 19, 20. The data at dnormaltable=120mm and over all d FG reported in Fig.…”
Section: Discussionmentioning
confidence: 85%
“…A number of studies showed that EMT is a viable approach for quality assurance and implant tracking in brachytherapy 19. This study is the technical foundation of a recently initiated clinical investigation to study potential changes of the implant geometry in interstitial HDR brachytherapy of breast cancer by EMT.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations